2018
DOI: 10.4103/1793-5482.181115
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, treatment, and management strategy of meningioma during pregnancy

Abstract: The most common benign tumor of the brain is meningiomas. Usually diagnosed between the ages of 40–60, they are more common in women. Studies have shown a strong relationship between hormones and malignancies. Although meningiomas are slow-growing tumors of the brain, pregnancy seems to induce its growth speed. Studies concerning meningiomas and hormone relationship may explain the reason why symptoms during pregnancy flare. More specifically, the estrogen and progesterone receptor may take an active role thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…The mode of delivery should be discussed previously in a team of specialists, including an obstetrician, an anesthesiologist, and a neurologist. C-section is preferred and considered safer in preventing the stress induced by the Valsalva maneuver, which may further increase intracranial pressure (ICP) [ 1 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The mode of delivery should be discussed previously in a team of specialists, including an obstetrician, an anesthesiologist, and a neurologist. C-section is preferred and considered safer in preventing the stress induced by the Valsalva maneuver, which may further increase intracranial pressure (ICP) [ 1 ].…”
Section: Resultsmentioning
confidence: 99%
“…Prolactin receptors have also been found in meningiomas and are closely associated with the growth rate [ 1 ]. Due to the abundance of prolactin receptors that produce physiological pituitary hyperplasia, meningiomas are more likely to grow during and after pregnancy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Its occurrence during pregnancy is not different from adult population comprising about 20% of all brain tumors, with an incidence of 5-6 per 100,000 pregnancies. 4 However, studies have shown relationship between tumor growth and hormonal changes associated with pregnancy. These hormonal changes may be the reason of flaring up of symptoms during pregnancy.…”
Section: Discussionmentioning
confidence: 99%